Aktywizm konsumencki. Źródła ruchu i jego znaczenie w epoce antropocenu - Grenda, Magdalena (Humaniora. Czasopismo Internetowe, 2025)
Consumer activism is an important element of the contemporary business landscape that influences corporate strategies. The rise of environmental awareness among consumers compels companies to reflect on their actions and to implement more responsible practices. Consequently, consumer activism not only has a moral dimension but also, in relation to the company, a strategic value, i.e. a real impact on the long-term success or failure of the company. The article attempts to answer basic questions. What is a conscious consumerism? What threats of the modern world does it respond to? What are its types? Do the actions of this movement have a real impact on the challenges associated with the Anthropocene Era?